Alkylation of Histidine Residues of Bothrops jararacussu Venom Proteins and Isolated Phospholipases A2: A Biotechnological Tool to Improve the Production of Antibodies. (11th May 2014) - Guimarães, C. L. S.; Andrião-Escarso, S. H.; Moreira-Dill, L. S.; Carvalho, B. M. A.; Marchi-Salvador, D. P.; Santos-Filho, N. A.; Fernandes, C. A. H.; Fontes, M. R. M.; Giglio, J. R.; Barraviera, B.; Zuliani, J. P.; Fernandes, C. F. C.; et al.
Abstract : Crude venom of Bothrops jararacussu and isolated phospholipases A2 (PLA2 ) of this toxin (BthTX-I and BthTX-II) were chemically modified (alkylation) by p -bromophenacyl bromide (BPB) in order to study antibody production capacity in function of the structure-function relationship of these substances (crude venom and PLA2 native and alkylated). BthTX-II showed enzymatic activity, while BthTX-I did not. Alkylation reduced BthTX-II activity by 50% while this process abolished the catalytic and myotoxic activities of BthTX-I, while reducing its edema-inducing activity by about 50%. Antibody production against the native and alkylated forms of BthTX-I and -II and the cross-reactivity of antibodies to native and alkylated toxins did not show any apparent differences and these observations were reinforced by surface plasmon resonance (SPR) data. Histopathological analysis of mouse gastrocnemius muscle sections after injection of PBS, BthTX-I, BthTX-II, or both myotoxins previously incubated with neutralizing antibody showed inhibition of the toxin-induced myotoxicity. These results reveal that the chemical modification of the phospholipases A2 (PLA2 ) diminished their toxicity but did not alter their antigenicity. This observation indicates that the modified PLA2 may provide a biotechnological tool to attenuate the toxicity of the crude venom, by improving the production of antibodies and decreasing the local toxic effects of this poisonous substance in animals used to produce antivenom.